Presidential Address (Nepalese Linguistics, 2022)
This presidential address raises issues in language policy of Nepal regarding multiple official languages in the government business. Implementation of this policy requires language of record and a group of government staff to work on different languages. By creating jobs for hundreds of linguists, this solution addresses the university officials' concern about decreasing number of students in linguistics.